The strategic perspectives of using GIS-technologies for creation of integrative Antarctic geo-base of scientific data - Seredinin, E.; Morgun, S.; Kurenkov, V.; Tashyrev, A.; Kobzar, L. (Ukrainian Antarctic Journal, 2009)
Strategic prospects use GIS technologies are presented in report for making integrated geodatabase of scientific data, designed on base of the lifelengths operating in the field of automations of the information handling in National antarctic scientific centre MES of Ukraine (NASC). It is shown, that given decision effectively, in good time, corresponds to the world standard of the collection, processing and presentation of scientific data.